Renoprotective Activity of Morinaga Oleifera Lamk Toward Kidney Injury Rats Induced by Streptozotocin - Giovani Gianosa; Suryono Suryono; Ali Santosa (NurseLine Journal, 2022)
Diabetes mellitus (DM) is a group of metabolic diseases characterized by hyperglycemia that occurs due to abnormalities in insulin secretion. Chronic hyperglycemia in diabetes causes dysfunction and failure of various organs of the body such as the kidneys, eyes, nerves, heart and blood vessels. The purpose of this study was to analyze how the effect of the treatment given by Moringa leaves on diabetes mellitus conditions, especially on glomerular histopathological damage. In this study, to make diabetic mice using the induction of streptozotocin after which Moringa leaves were given as a form of treatment. The dosage of Moringa leaf extract was divided into 5 groups, namely 62.5mg / kg, 125mg / kg, 250mg / kg, 500mg / kg, and 1000mg / kg doses. The histopathological image obtained will be assessed using scoring, and for data analysis using the Kruskal-Wallis test and followed by the post hoc test using the Mann-Whitney test. The results of this study indicate that there is an effect of giving Moringa leaf extract on glomerular histopathological damage. The results of the Kruskal-Wallis data analysis test showed significant results, namely p = 0.001, after the data obtained were significant data, then it was continued with the post hoc test using the Mann-Whitney test with significant results when compared with negative controls ranging from the 125mg / kg dose group 1000mg / kg.